The Perceptions of white UOF students with regard to the general black population - Liesel Manthe; Manie Breytenbach (Communicare)
A central leque ini Intercultural interaction is the phenomenon of per ception. Perception Influences the understanding and Interpretation of events. In order to succeed in Inter cultural Interaction it is necessary to develop an understanding and ap preciation of perceptual differences. The purpose of this study was to examine the perceptions that a sec tion of white UOFS students have of the general black population. To reach this objective, a literature study was undertaken in order to es tablish a clear understanding of per ception and the related concepts. Such concepts included race, cul ture, attitude, prejudice and stereo type. The study concentrated on the Interrelations between these con cepts as well as on the effects of these concepts on the formation of an Individual's perceptions. Through statistical analysis the following considerations were also ad dressed: Whether or not any correlations exist between the perceptions of the respondents. Whether male and female re spondents differ with regard to their political orientations. Whether there are any differences and/or similarities in the perceptions of male and female respondents. • The Identification of specific fac tors in order to determine their contribution toward specific perceptions